Follow-up on Assessment of Student Outcomes by Senior-Year Design Project and Continuing to Improve by Performance Indicator Breakdown-Based Assessment - Dulekgurgen, Ebru; Yangin-Gomec, Cigdem; Karahan Ã–zgün, Özlem; Aydin, Basak; Guven, Huseyin (International Journal of Engineering Pedagogy (iJEP), 2018)
The study is a follow-up on rubric-based assessment of level of attainment of Student Outcomes (SOs) in Environmental Engineering undergraduate education by the senior-year Graduation Design Project (GDP): the focal points are the process of and results from incorporation of additional assessment tools and implementation of “Performance Indicator (PI)-breakdown” approach to continue improving the SO Assessment and Evaluation (A&E) process. For several consecutive cycles, A&E to define attainment level of total of seven SOs by the GDP gave results below the set thresholds for some of them (SO1,5,8), which indicated a discrepancy and a need for improvement not only in the assessment tools, but also in the A&E processes. Accordingly, two remedial actions were undertaken to meet those needs and the SOs were re-assessed. As the first remedial action, alternative assessment tools were incorporated to the SO A&E process. Assessment results revealed a clear progress in SO attainment, from 2014-15 to 2015-16. However, those lump-sum results still gave a general sense of students’ performance at SO-level. Therefore, some additional assessment tools were added and the “PI-breakdown”-based approach was implemented as the second remedial action. Those implementations enabled obtaining more realistic, detailed, and in-formative results and facilitated further fine tuning of the SO A&E process.